Cover crop and tillage intensities alter ground-dwelling arthropod communities during the transition to organic production. Issue 4 (12th August 2015) - Jabbour, Randa; Pisani-Gareau, Tara; Smith, Richard G.; Mullen, Christina; Barbercheck, Mary
Abstract: We conducted a cropping systems experiment in central Pennsylvania, USA, to determine the effects of initial cover crop species and soil management on the abundance and composition of the ground-dwelling arthropod community. We hypothesized that we would detect legacy effects of the cover crops planted in year 1 of a 3-yr crop sequence on the arthropod community in the subsequent 2 yrs, and that these effects would be influenced by the intensity of tillage. We compared four systems in a factorial combination of perennial sod and legumes or annual cereal grain and legume as initial cover crops and moldboard or chisel plow tillage implemented in soybeans followed by maize in the subsequent 2 yrs. The entire experiment was initiated twice in adjacent locations, starting in 2003 (Start 1) and 2004 (Start 2). We quantified soil arthropod activity-density and community composition and identified all arthropods to order or family, and the ground and tiger beetles (Coleoptera: Carabidae) to species. In Start 1, but not Start 2, arthropod activity-density increased with each year following implementation of organic management. We observed few legacy effects of cover crop or tillage intensity on arthropod activity-density. The composition of the soil arthropod community was primarily defined by the initial cover crop in the first year, and by the interaction between cover crop and tillage intensity in the second and third year. A legacy effect associated with a yr-1 cover crop of cereal rye was observed for Scarabaeidae beetles and Formicidae (ants) in yr 2 and Carabidae beetles in yr 3 of Start 1, but not Start 2. Weed indicators contributed significantly to the variation in the soil arthropod community that was explained by the environment in yr 2 in Start 1, and in yr 3 in both Starts. Our observations support the concept that both immediate and legacy effects of management shape arthropod communities during the organic transition period, suggesting that transitioning systems could be managed in ways that conserve or enhance natural enemy populations.